Microbiological and Nutritional Analysis of Lettuce Crops Grown on the International Space Station - Khodadad, Christina L. M.; Hummerick, Mary E.; Spencer, LaShelle E.; Dixit, Anirudha R.; Richards, Jeffrey T.; Romeyn, Matthew W.; Smith, Trent M.; Wheeler, Raymond M.; Massa, Gioia D. (Frontiers in Plant Science, 2020)
The ability to grow safe, fresh food to supplement packaged foods of astronauts in space has been an important goal for NASA. Food crops grown in space experience different environmental conditions than plants grown on Earth (e.g., reduced gravity, elevated radiation levels). To study the effects of space conditions, red romaine lettuce, Lactuca sativa cv 'Outredgeous', plants were grown in Veggie plant growth chambers on the International Space Station (ISS) and compared with groundgrown plants. Multiple plantings were grown on ISS and harvested using either a single, final harvest, or sequential harvests in which several mature leaves were removed from the plants at weekly intervals. Ground controls were grown simultaneously with a 24-72 hour delay using ISS environmental data. Food safety of the plants was determined by heterotrophic plate counts for bacteria and fungi, as well as isolate identification using samples taken from the leaves and roots.